1998
DOI: 10.1093/emboj/17.7.1941
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Rab-binding domains mediate the interaction of Rabaptin-5 with GTP-bound rab4 and rab5

Abstract: Rabaptin-5 functions as an effector for the small GTPase Rab5, a regulator of endocytosis and early endosome fusion. We have searched for structural determinants that confer functional specificity on Rabaptin-5. Here we report that native cytosolic Rabaptin-5 is present in a homodimeric state and dimerization depends upon the presence of its coiledcoil predicted sequences. A 73 residue C-terminal region of Rabaptin-5 is necessary and sufficient both for the interaction with Rab5 and for Rab5-dependent recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
218
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(233 citation statements)
references
References 42 publications
14
218
1
Order By: Relevance
“…To test the specificity of Rab5 involvement, we also examined Rab4, which mediates receptor recycling between early endosomes and the plasma membrane. Rabaptin-5 binds to the active form of Rab4 at its N terminus (25). As shown in Fig.…”
Section: Gsk-3 Regulation Of Ampars Involves the Stimulation Of The Gmentioning
confidence: 98%
“…To test the specificity of Rab5 involvement, we also examined Rab4, which mediates receptor recycling between early endosomes and the plasma membrane. Rabaptin-5 binds to the active form of Rab4 at its N terminus (25). As shown in Fig.…”
Section: Gsk-3 Regulation Of Ampars Involves the Stimulation Of The Gmentioning
confidence: 98%
“…Initially, rabaptin-5 was identified as an interactor of rab5 (Stenmark et al, 1995) and rabex-5 as a rab5 guanine nucleotide exchange factor (Horiuchi et al, 1997). Rabaptin-5 in addition was shown to bind to rab4 and AP-1 (Vitale et al, 1998;de Renzis et al, 2002;Deneka et al, 2003). On immunodepletion of rabaptin-5/rabex-5 from the cytosol with an anti-rabaptin-5 antibody ( Figure 8A), formation of endosomal vesicles was reproducibly stimulated (Figure 8B), suggesting an inhibitory role of the complex.…”
Section: Rab4 and Rabaptin-5/rabex-5 Regulate The Formation Of Recyclmentioning
confidence: 98%
“…Rabenosyn-5 and rabaptin-5/rabex-5 have been shown to be interaction partners of rab4 as well as rab5 (Vitale et al, 1998;de Renzis et al, 2002). The fact that these proteins can simultaneously bind to both active rab GTPases suggested that they regulate endosomal protein sorting and recycling by defining and connecting endosomal subdomains (de Renzis et al, 2002).…”
Section: In Vitro Formation Of Recycling Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations